ALI MUSTAFA YA’QUB: CRITICISM OF PROBLEMATIC HADITH AND ITS CONTRIBUTION TO THE DEVELOPMENT OF THE STUDY OF HADITH IN INDONESIA - Alfani Hidayat; Faida Fidiani (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
This article discusses Ali Mustafa Ya'qub's criticism of the popular hadiths in society and their contribution to the development of hadith studies in Indonesia. Ali Mustafa Ya'qub tested the authenticity of these problematic hadiths by combining sanad and matan criticism. The results of this study comprehend Ali Mustafa Ya'qub's method of understanding a hadith by referring to the hadith Takhrij, namely by referring to the work of Mahmud Thahhan. In addition, he also often performs ijtihad independently in determining the quality of hadith, namely by looking at the opinions of mutaqaddimin, mutaakhkhirin and contemporary scholars. Ali Mustafa Ya'qub's contribution to the study of hadith in Indonesia can be seen based on his critical attitude when he studied and criticized the work of orientalists, namely Ignaz Goldziher, Juynboll, Joseph Schact and David Samuel Margolioth as well as scholars who went against the flow. He also verified the hadith and also founded the Darussunnah Islamic Boarding School in the hope that it would produce muhaddiths and become an asset in understanding hadith.